A transformed radial stub low-pass filter using defected ground structure for stopband extension - Xu, Shanshan (2015)
The paper presents a low-pass filter using defected ground structure for stopband enhancement. The face-to-face E shape defected ground structure is investigated using EM simulation, which are co-designed with transformed radial stub low-pass filter to extend the stopband. The fabricated filter demonstrates a passband insertion loss of less than 1 dB, a wide stopband with more than 20 dB rejection up to 16ƒc (ƒc is the cut-off frequency of 2.4 GHz), a passband return loss of better than 20 dB, and a compact size of 5×1.3 cm2 only.